Antimicrobial activity assessment of crude broth fermented extracts of marine-derived fungi collected from Bai Tu Long Bay (North Vietnam) - Nguyen Thi Hoang Anh, Nguyen Thi Hoang Anh; Vu, Thi Thu Huyen; Nguyen, Mai Anh; Doan, Thi Mai Huong; Pham, Van Cuong; Dam, Thanh Xuan; Cao, Duc Tuan; Le, Thi Hong Minh (Vietnam Journal of Marine Science and Technology, 2024)
This study aimed to isolate and identify marine fungi from Bai Tu Long Bay and assess their antimicrobial potential. We successfully isolated twenty strains of marine-derived fungi. The crude extracts from these fungi were tested against pathogenic microorganisms. All twenty strains exhibit some degree of growth inhibition against the tested microorganisms. Notably, strains M223, M250, M253, and M256 showed significant antimicrobial activity, with MIC values equal to or lower than the positive control. These results highlight the potential of marine fungi as a rich source of antimicrobial agents, a finding of considerable importance to marine mycology and pharmaceuticals. Further analysis was conducted on four promising isolates. M253 was identified as Hamigera avellanea, while M223, M250, and M256 were found to belong to the Aspergillus genus. These isolates were then analyzed using a phylogenetic tree based on MegaX software.